2014
DOI: 10.1097/iop.0000000000000281
|View full text |Cite
|
Sign up to set email alerts
|

The BLICK Mnemonic for Clinical–Anatomical Assessment of Patients With Epiphora

Abstract: The BLICK mnemonic is a useful adjunct to the workup of epiphora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…This group includes entropion, ectropion, trichiasis/distichiasis, and other less common problems which were reported by Tse et al [15]. The authors especially specified the importance of blinking and the factors that effect this mechanism.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This group includes entropion, ectropion, trichiasis/distichiasis, and other less common problems which were reported by Tse et al [15]. The authors especially specified the importance of blinking and the factors that effect this mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, such pathologies included mass closing punctum, conjunctivochalasis, inflamed pterygium, and double punctum anomalies, all of which had a 2.4% (4/163) rate. Conjunctivochalasis is an interesting condition that causes epiphora by mechanically displacing the normal tear meniscus and impeding the flow along the eyelid margin toward the punctum [15]. These rare causes varied between 0.7% and 5.1% in other studies [2, 7].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that eyelid disorders, including entropion, ectropion, trichiasis, and conjunctivochalasis, may induce epiphora. 16 Ectropion may cause the punctum to move away from the bulbus, thus obstructing lacrimal drainage. In entropion, the lid margin turns inward toward the ocular surface and may damage the cornea and conjunctiva, causing reflex tearing.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, conjunctivochalasis may cause epiphora by mechanically displacing the normal tear meniscus and impeding tear flow along the eyelid margin toward the punctum. 16 …”
Section: Discussionmentioning
confidence: 99%
“…1 Epiphora is four times more common in women than in men, 2 and its prevalence ranges from 9% to 10% at 50 years old to 35–40% at 90 years old. 3 The differential diagnosis for epiphora is broad and includes reflex tearing from dry eye, with compensatory hypersecretion, 4 poor tear distribution due to altered blink dynamics and lid malposition, 5 and defective tear drainage from stenosis of the nasolacrimal drainage system. 6 The etiology of nasolacrimal duct obstruction may be primary (idiopathic) 7 or secondary, due to a variety of causes, including local inflammation or fibrosis ( e.g.…”
mentioning
confidence: 99%